Exceptional Values of Meromorphic Function on Annulus - Hong-Yan Xu (The Scientific World Journal)
The main purpose of this paper is to study the exceptional values of meromorphic function and its derivative on annulus. We also give some theorems and corollaries about exceptional values of meromorphic function on the annulus, which are the improvement of the previous results given by Chen and Wu.